Podzielić się nowoczesnością. Reparacje 2.0? - Gelles, Katarzyna; Kwieciński, Leszek; Michalski, Bartosz (Rocznik Polsko-Niemiecki, 2020)
This article embarks on a fresh and pragmatic look at German reparations for Poland. The analysis is based on a historical, neo-institutional and rational theory approach. It covers past and current experiences of the ‘reparations debate’. Then, in the context of Europeanisation processes and the Polish middle-income trap, the authors explain their original concept on how to identify areas of possible technological cooperation and provide recommendations. This strategic attempt to share modernity may enhance Polish economic development and enter the social and political debate as an effective means of Polish-German reconciliation.